7.6=(x)(x+5)(3x-1)

Simple and best practice solution for 7.6=(x)(x+5)(3x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7.6=(x)(x+5)(3x-1) equation:


Simplifying
7.6 = (x)(x + 5)(3x + -1)

Reorder the terms:
7.6 = x(5 + x)(3x + -1)

Reorder the terms:
7.6 = x(5 + x)(-1 + 3x)

Multiply (5 + x) * (-1 + 3x)
7.6 = x(5(-1 + 3x) + x(-1 + 3x))
7.6 = x((-1 * 5 + 3x * 5) + x(-1 + 3x))
7.6 = x((-5 + 15x) + x(-1 + 3x))
7.6 = x(-5 + 15x + (-1 * x + 3x * x))
7.6 = x(-5 + 15x + (-1x + 3x2))

Combine like terms: 15x + -1x = 14x
7.6 = x(-5 + 14x + 3x2)
7.6 = (-5 * x + 14x * x + 3x2 * x)
7.6 = (-5x + 14x2 + 3x3)

Solving
7.6 = -5x + 14x2 + 3x3

Solving for variable 'x'.

Reorder the terms:
7.6 + 5x + -14x2 + -3x3 = -5x + 5x + 14x2 + -14x2 + 3x3 + -3x3

Combine like terms: -5x + 5x = 0
7.6 + 5x + -14x2 + -3x3 = 0 + 14x2 + -14x2 + 3x3 + -3x3
7.6 + 5x + -14x2 + -3x3 = 14x2 + -14x2 + 3x3 + -3x3

Combine like terms: 14x2 + -14x2 = 0
7.6 + 5x + -14x2 + -3x3 = 0 + 3x3 + -3x3
7.6 + 5x + -14x2 + -3x3 = 3x3 + -3x3

Combine like terms: 3x3 + -3x3 = 0
7.6 + 5x + -14x2 + -3x3 = 0

The solution to this equation could not be determined.

See similar equations:

| 22=x-3 | | h=16t^2+70t+9 | | x/8+x/3=11/24 | | h=-16t+70t+9 | | -18+20x=2 | | 2.5y=55 | | 9x/2=-18 | | 4n/5-7/11=53/55 | | x/9-1=2 | | (m^2-9)/(m^2-6m+9) | | 8x-20=4x-4 | | 7=3x+6 | | 20=4x+20 | | 4/6-2=6 | | 8w+7=31 | | 11(z+2)-3(z-3)=4(2-3)+3(z-1) | | y=14-(5x-8) | | -19=-5x+12 | | -15=-4n+5 | | x^3+12x^2-3x-910=0 | | 10x-91=-107 | | 240-12x+x*x=0 | | 17x-(8x-4)=13 | | 5/6y=-20 | | -3x/8=-3 | | 2(5z+2)-6=88 | | (5x/8y^3)^2 | | x+24.8=48.5 | | 5(5x-1)=100 | | 40-2x=-38 | | 4x+9x-6x=42+7 | | 23=8x-9 |

Equations solver categories